Systematic literatur review: Eksplorasi etnomatematika pada rumah adat - Putri, Viola Amanda; Deswita, Ria; Anggraini, Reri Seprina (Journal of Smart Education and Learning, 2024)
Ethnomathematics, which examines the relationship between mathematics and culture, has become a focus of study in recent years, including in the context of traditional house architecture. This article explores the mathematical concepts in designing and constructing traditional houses through a systematic literature review approach. Various studies show that mathematical elements, such as geometry, symmetry and proportionality, are present in the structure and ornamentation of traditional houses. For example, the Minangkabau traditional house (Rumah Gadang) applies the triangle principle to the roof for stability, while the Toraja traditional house uses symmetry in the roof. This research aims to identify mathematical concepts used by local communities in designing traditional houses and their potential application in mathematics learning. Through this exploration, it is hoped that this article can provide new insights into integrating mathematical knowledge into the daily lives of traditional communities and encourage the development of more culturally relevant educational curricula. Thus, this research contributes to preserving cultural heritage and enriching locally based mathematics education.